Post-operative renal failure management in mechanical circulatory support patients - Austin, Danielle (Ann Transl Med, 2020)
Acute kidney injury (AKI) occurs commonly in patients requiring mechanical circulatory support (MCS) after cardiothoracic surgery. The prognostic implications of AKI in this patient group relate closely to the pathophysiology and risk factors associated with the underlying disease; pre-operative, intra-operative, and post-operative variables; hemodynamic factors; and type of support device used. General approaches to AKI management, including prevention strategies, medical management, and hemodynamic support, are also applicable in patients requiring MCS. Approaches to renal replacement therapy vary depend on patient factors, device-specific factors, and local preferences and experience. In this invited narrative review, we discuss the pathophysiology, risk factors, and prognostic implications of AKI in post-operative adult patients following institution of MCS. Management strategies for AKI are presented with a focus on those supported with either extracorporeal membrane oxygenation or a ventricular assist device.